Design and immunogenic evaluation of multi-epitope vaccines for colorectal cancer: insights from molecular dynamics and In-Vitro studies - Sun, Peiwei; Wang, Luolin; Liu, Zhong; Xu, Zhenglei (Frontiers in Oncology, 2025)
BackgroundThis study aimed to identify cytotoxic T lymphocyte (CTL)-specific epitopes from three tumor-associated antigens (TAAs)—Dickkopf-like 1 (DKKL1), F-box protein 39 (FBXO39), and Opa-interacting protein 5 (OIP5)—which are overexpressed in colorectal cancer (CRC), as potential candidates for CTL-mediated immunotherapy.MethodsThe amino acid sequences of DKKL1, FBXO39, and OIP5 were analyzed to predict high-affinity CTL epitopes using the NetCTL server. Their antigenicity, allergenicity, conservation, and glycosylation potential were assessed for safety and effectiveness. Cross-reactivity and binding affinities were evaluated through molecular docking. Two multi-epitope vaccine constructs were designed incorporating the CTL epitopes, GM-CSF and IL-2 adjuvants, and a PADRE sequence. Docking studies with Toll-like receptor 4 (TLR-4) were performed. In-vitro assays using human peripheral blood mononuclear cells (PBMCs) were conducted to evaluate the immunogenicity of the vaccine constructs, focusing on cytokine release and T-cell activation. Additionally, molecular dynamics simulations were performed to assess the stability of peptide-HLA interactions.ResultsHigh-affinity CTL-specific epitopes were successfully identified from DKKL1, FBXO39, and OIP5, showing strong binding potential to HLA class I molecules. The selected epitopes were predicted to be non-allergenic, non-glycosylated, and conserved across species. Molecular docking confirmed stable binding interactions between the epitopes and HLA alleles. In-vitro validation demonstrated that PBMCs stimulated with the multi-epitope vaccine constructs produced significant increase in cytokine levels, including IFN-γ and IL-2, indicative of robust CTL activation. Moreover, molecular dynamics simulations showed strong and stable binding affinities between the epitopes and HLA molecules, suggesting effective antigen presentation. Additionally, docking studies revealed strong binding affinities between the vaccine constructs and TLR-4, suggesting their potential to trigger a strong immune response.ConclusionThis study identified CTL-specific epitopes from DKKL1, FBXO39, and OIP5 as potential targets for colorectal cancer immunotherapy. The multi-epitope vaccine constructs exhibited significant immunogenic potential, providing a foundation for future clinical validation. These findings underscore the promise of these TAAs as key targets for CTL-based vaccine development in colorectal cancer.